Fermented foods and metabolic outcomes in diabetes and prediabetes: A systematic review and meta-analysis of randomized controlled trials - Zhang, Xiao-Feng; Qi, Yue; Zhang, Yong-Ping; Deng, Jin-Lan; Chen, Xiao-Li; Li, Ruo-Nan; Zhou, Qi-Lun; Fan, Jian-Ming (Critical reviews in food science and nutrition, 2024)
Several randomized controlled trials (RCTs) have investigated the effects of fermented foods on metabolic outcomes in adult patients suffering from diabetes and prediabetes. However, the results of these RCTs are conflicting. This systematic review and meta-analysis was carried out on data from RCTs to evaluate the effects of fermented foods in patients with diabetes and prediabetes. The PubMed, Web of Science, Embase, the Cochrane Library and Scopus databases were searched up to 21 June, 2022. English-language RCTs of fermented foods consumption were included which gave metabolic outcomes on body composition, glucose control, insulin sensitivity, lipid profile, as well as blood pressure. Eighteen RCTs met the inclusion criteria and 843 participants were included in the final analysis. The pooled results showed a significant reduction of fasting blood glucose (FBG), the homeostatic model assessment of insulin resistance (HOMA-IR), total cholesterol (TC), low density lipid cholesterol (LDL-C) and diastolic blood pressure (DBP) in the intervention group versus the control group. The results of this research showed that fermented foods have the potential to improve some metabolic outcomes, including FBG, HOMA-IR, TC, LDL-C, and DBP in patients with diabetes and prediabetes.